Intimate Partner Violence Among Hong Kong Young Adults: Prevalence, Risk Factors, and Associated Health Problems. (August 2015) - Zhang, Huiping; Wong, William C. W.; Ip, Patrick; Fan, Susan; Yip, Paul S. F.
Intimate partner violence is a serious social problem and public health issue affecting the well-being of the young adults. However, there is very little epidemiological evidence on the incidence and associated health problems in contemporary Chinese society. Using a representative community sample of 1, 223 young adults aged 18 to 27 years conducted by Hong Kong Family Planning Association in 2011, this study aimed to estimate the prevalence, risk factors, and possible health consequences of intimate partner violence among young adults in Hong Kong. It is found that the prevalence of lifetime and preceding 1-year intimate partner violence by former or current partners was 8.6% and 4.9% respectively. Male youths who were older were less likely to experience past-year intimate partner violence (odds ratio [OR] = 0.21, p < .05) and those who had a university degree or were unemployed were more likely to experience past-year intimate partner violence (OR = 8.48, p < .01 and OR = 8.14, p < .05 respectively). Female youths who had a full-time job were less likely to experience the lifetime violence (OR = 0.15, p < .05) and those who were ever pregnant with current partner were more likely to experience both lifetime intimate partner violence (OR = 5.00, p < .05) and past-year violence (OR = 5.63, p < .05). Both female and male victims were more likely to be subjected to mental health problems and only female victims felt fear for the violent partner.